Phytochemical screening and purification of Xoi from selected medicinal plant - Jamal, Parveen; Amid, Azura; Abdullah, Suhana (IIUM Press, 2011)
Xanthine oxidase is an enzyme lhal catalyzes lhe oxidalion ofxanlhine 10 unc acid. which will be lhe cause of gout. Allopurinol is a medicine to cure gout nowadays. bUI il has many drawbacks. This slUdy a1H:mpls to cvaluale three local medicinal planls for their polentiallO be an alternative to allopurinol. The plan! species were Labisia pumila. !!fell/lla spica/a and LycopersiCOll esculenlu1ll. The results have re\'caled lhat methanolic cxtracl of Lrco['('rsicOll eSClIlemllm leaves has lhe highest XO inhibilory activity with 89.61 %. Therefore. it was selecled for the isolalion and purification of the bioaclive componenl lhal may be responsible for lhe said aClivity via two chromalographic procedures. namely, column chromatography aJld thin layer chromalography. One Spol was reco,·ered from Ihe separation via column chromalography ulilizing 8% MeOH - CHell as the elution system. Thc Rr value oblained via TlC for lhe Spol is 0.813.